2009
DOI: 10.1007/s10518-009-9139-0
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response of nonstructural components in case of nonlinear structures based on floor response spectra method

Abstract: This paper investigates the response of nonstructural components in the presence of nonlinear behavior of the primary structure using floor response spectra method (FRS). The effect of several parameters such as initial natural frequency of the primary structure, natural frequency of the nonstructural components (subsystem), strength reduction factor and hysteretic model have been studied. A database of 164 registered ground acceleration time histories from the European Strong-Motion Database is used. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 6 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…A comprehensive state‐of‐the‐art review on the seismic design of NSCs in context of regular buildings has already been reported in earlier studies . Past studies on the evaluation of floor acceleration demands can be broadly classified under the categories of studies based on both single‐degree‐of‐freedom and multiple‐degree‐of‐freedom modeling of the supporting structure. The parameters affecting the floor response, identified in these studies, include the dynamic characteristics (periods and mode shapes) of the supporting structure, the input seismic ground motion characteristics, and the inelasticity (ductility demand) of the supporting structure .…”
Section: Background Studiesmentioning
confidence: 99%
“…A comprehensive state‐of‐the‐art review on the seismic design of NSCs in context of regular buildings has already been reported in earlier studies . Past studies on the evaluation of floor acceleration demands can be broadly classified under the categories of studies based on both single‐degree‐of‐freedom and multiple‐degree‐of‐freedom modeling of the supporting structure. The parameters affecting the floor response, identified in these studies, include the dynamic characteristics (periods and mode shapes) of the supporting structure, the input seismic ground motion characteristics, and the inelasticity (ductility demand) of the supporting structure .…”
Section: Background Studiesmentioning
confidence: 99%
“…The main parameters that govern the dynamic response of the 2SDOF system representing the main structure and NSC ( Figure 1) can be easily derived from Equation (1). As matter of fact, the mass ratio ma/m, as well as other parameters usually considered for simulating the response of SDOF systems can be identified as key parameters controlling the response of both the main structure and the NSC: The system represented in Figure 1 allows to consider the coupled behavior of the main structure and NSC and can result more appropriate than systems generally adopted in similar studies which are often based on the dynamic analysis of two uncoupled single-degree-of-freedom (SDOF) systems in series [20,21]. As matter of fact, the latter systems are based on the simulation of a SDOF system representing the main structure whose response is, subsequently, considered as the ground motion for the secondary SDOF system which simulates the NSC.…”
Section: Parametric Investigationmentioning
confidence: 99%
“…Moreover, more consistent response parameters can also be defined for describing the dynamic response of NSCs. For this purpose, [20,21] defined the following two parameters…”
Section: Definition Of Relevant Response Parametersmentioning
confidence: 99%
“…They are based on empirical variation of peak floor accelerations (PFAs) throughout the height of a building. Several authors have questioned the suitability of the code formulae and proposed various improvements to them, for example, [4][5][6] for Eurocode 8, [7][8][9][10] for ASCE 7-10 and its predecessors, and [11] for the National Building Code of Canada (NBC 2005) [12]. A simple method that is similar to the code procedures was also proposed by Villaverde [13].…”
Section: Introductionmentioning
confidence: 99%